Herder's Political Thought : A Study on Language, Culture and Community - Spencer, Vicki A., 1961- (Book collections on Project MUSE., 2012)
Vicki A. Spencer reveals Herder as one of the first Western philosophers to grapple seriously with cultural diversity without abandoning a commitment to universal values and the first to make language and culture an issue of justice. As Spencer argues, both have made Herder a source of inspiration for the pluralist turn of contemporary political philosophy. Contending that in an era of globalization, it is no longer possible to ignore Herder's crucial insights on the relationship between cultural membership and individual identity, Spencer demonstrates how these ideas can help us understand, and perhaps resolve, the linguistic and cultural-political struggles of our times"--